Mechanistic origin of high-cycle fatigue enhancement by grain refinement in AZ81 magnesium alloy for sports equipment - Dong Li; Liuyong He (PLoS ONE, 2026)
Lightweight, high-strength alloys are increasingly demanded in sports equipment. Magnesium (Mg) alloys are attractive due to their low density and high specific strength. This study systematically investigates the grain size–dependent high-cycle fatigue (HCF) behavior of AZ81 Mg alloy with comparable basal textures. The fine-grained (FG, ~ 8 μm) sample exhibits significantly improved mechanical performance compared with the coarse-grained (CG, ~ 62 μm) counterpart. The yield strength increases from 134.2 MPa to 164.5 MPa (~22.6%), and the ultimate tensile strength rises from 231.7 MPa to 283.7 MPa (~22%), while maintaining comparable ductility. More importantly, the fatigue strength at 10⁶ cycles increases from 80 MPa to 110 MPa, representing a 37.5% enhancement. Microstructural analyses reveal that grain refinement suppresses extension twinning and persistent slip band formation, while promoting the activation of <c + a> and non-basal dislocations. The FG microstructure also contains finer and more uniformly distributed Mg 17 Al 12 precipitates, facilitating Orowan strengthening. These combined effects reduce strain localization and delay fatigue crack initiation. The findings clarify the mechanistic origin of grain refinement–induced fatigue enhancement and provide guidance for the design of Mg alloys in weight-critical sports applications.